Synthesis of block copolymers by combined ultrasonic irradiation and reverse atom transfer radical polymerization processes - Degirmenci, Mustafa; Catalgil‐Giz, Huceste; Yagci, Yusuf (Wiley, 2003)
AbstractA two‐step procedure based on ultrasonic irradiation and reverse atom transfer radical polymerization (RATRP) for the synthesis of block copolymers is described. In the first step of the procedure, a stable chlorine‐end‐capped polymer is formed upon the ultrasonic irradiation of poly(methyl methacrylate) (PMMA) in dry benzene in the presence of a copper chloride/2,2′‐bipyridine catalyst. Heating the system to 110 °C initiates the polymerization of the second monomer, styrene, and this results in the formation of the block copolymers. The degradation behavior of PMMA under ultrasonic irradiation has also been studied. The agreement of the experimentally obtained molecular weights and theoretical molecular weights and the unimodal shapes of the gel permeation chromatography curves of the block copolymers indicate the controlled nature of the RATRP process initiated by polymeric radicals formed by sonication. © 2003 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 42: 534–540, 2004